Studi Eksperimental Pergerakan Temperatur Radiator Terhadap Putaran Mesin (RPM) dengan Kecepatan Kipas Constant - Prasetyo, Andi; Surono, Arif (Creative Research in Engineering (CERIE), 2021)
The research aims to evaluate the engine rotation (rpm) against changes in radiator temperature. Radiator used is compact heat exchanger tube and fins type. The study was conducted using an experimental method on a BMW E.36 car with a stop state. The research scheme we use consists of radiator water reservoir tanks, water pumps, and radiators. Measuring instruments used are anemometer, thermocople, stopwatch and reader. Data retrieval is carried out at the radiator entrance temperature, radiator exit temperature and the temperature on the radiator wall that hits the fan. In this study we did variations of engine rotation (rpm) of 1000, 1500, 2000, 2500 and 3000 rpm. The results showed that in the use of fans at a speed of 6.5 m / s able to throw heat into the environment well, this proved to be obtained the highest temperature value at the 10th minute of 57.5 oC at a fan speed of 3.5 m / s. Meanwhile, in the 10th minute the lowest temperature was obtained from a speed of 6.5 m/s of 40 oC.